International Prices, Wages and Inflation in an Open Economy: A Chilean Model - Corbo, Vittorio (The Review of Economics and Statistics, 1985)
This paper presents a macroeconomic model to explain the dynamics of Chilean inflation during 1976-82. The model extends the Australian and Scandinavian open economy models by making a finer distinction between tradables and nontradables and by introducing more elaborate expectations formation. Results of the model supplied to quarterly Chilean data over the period reject the homogeneity of the system indicating that a devaluation does indeed affect the relative price between tradables and nontradables in the Chilean context. The results cast doubt on the stabilization policies pursued during the period 1979-82, which implicitly relied upon a model in which full homogeneity obtains.